(untitled) (Archives of Criminology, 1988)
The Act on the treatment of persons evading work was passed on November 26, 1982 and entered into force on January 1, 1983. The passing of the Act was preceded by a period of heated discussions during which the need for this regulation or objections against it were justified by various social, economic, political legal as well as philosophical reasons. The Act bound all men aged 18-45 (with the exception of some clearly defined categories) who neither work nor learn for a period of at least 3 month and who are not registered in employment agencies as looking for a job to report at the local state administrative agencies and explain the reasons of this state of affairs. Such persons can be recognized as not working for justified reasons (in this case, they should get help if needed) or for unjustified reasons (to such persons the possibilities of taking the job should be pointed out; they should also get help if needed). Man who persistently evade work and whose sources of maintenance cannot be revealed or prove to be contradictory to the principles of social existence, are included in a list of persons who persistently evade work. The law provides for the following legal consequences towards persons who fall under its provisions: a failure in the duty to report is a transgression for which there is a penalty of limitation of liberty of up to three months; the same penalty is provided for the registered person’s failure to appear when summoned by the local administrative agency: a failure of a registered person in the duty to appear when summoned in order to make a statement concerning his sources of maintenances is an offence for which a penalty of limitation of liberty or a fine is provided; the persons who have been included in the list may be obligated to perform the work for public purposes in cases of force majeure or natural calamity that constitutes a serious threat for the normal conditions of the people’s existence; a failure in this duty is an offence for which a statutory penalty is that of limitation of liberty up two years or a fine. The Act deals with only one of the many and varied problems that result from the broad and multifarious issue of work: the situation of not being formally employed. Employment is connected with the actual policy in this respect, the labour market, and with many economic problems. The passing of the Act and the period of its functioning discussed in the present paper fell in Poland on the days of a profound socio-economic crisis which influences the problems related to employment. In our study, however, we have taken no account of the above broader issues, focusing on the functioning of the Act: the nation of , evasion of work’’ and , a person evading work’’ it introduced, the extent of the population that falls under the Act, characterization of the population mentioned the institutions and persons involved in realization of the Act, ways of dealing with the persons evading work, conformability of the conduct of the Act’s addresses with the model of conduct it includes, appraisal of the degree to which the aims of the Act, as set before it by the legislator have been reached, and the social effects of the law. The study concerned the functioning of the Act in the capital city of Warsaw. The basic source of information were index cards of all man evading work that had been registered in this territory in the period from January 1, 1983, till April 30, 1984. Moreover, district constables of the police were interviewed about these men; data concerning their criminal records were obtained from the Central Criminal Register and information about their detention in the Warsaw sobering-up station was obtained from the station’s files. Two years later, additional data were gathered in order to check which of the registered men worked for at least 6 month after having been registered; the course of work for public purposes done by the examined persons was also checked with enterprises that organized such work. In the period included in the study, 2,195 men evading work were registered in Warsaw. The size of this population seems susceptible of various interpretations, depending on the adepted point of view. This number however seems insignificant as compared with that of situations vacant reported at the employment agency which for instance exceeded 18 thousand jobs for men on December 31, 1983. As shown by the analysis of the course of registration in the entire examined period, and of the differences in the sizes of the registered populations in the separate Warsaw districts, the sizes in question vary greatly and depend on administrative steps that influence the revealing of men who answer the statutory definition. The term "person evading work" designates various persons whose various circumstances - whether socially accepted or not – justify their lack of permanent employment, and who find themselves in various situations. They are e.g. persons waiting to be called up, those who help their families with farming, alcoholics who find it impossible to keep any permanent job, men supported by their familes and looking after a family member, those who are preparing for examination to enter the university, those taking a rest after release from prison, and those who actually do work (there were about 1/4 of them): casually, seasonally or in private firms, but fail to settle their situation formally. According to the police data, as few as every tenth of the examined persons had among others, though not exclusively, illegal sources of maintenance such as offences or illicit trade. In general, the men registered as evading work did not differ from the entire population of men aged 18-45 who lived in Warsaw at that time as regards the age structure. There were among them relatively few married men. Their level of education was somewhat lower as compared with men employed at that time in Warsaw in the socialized economy; yet two-thirds of them were trained in some profession. According to the police inquiries, and to the information from index cards and from sobering-up station, three-fourth of the examined persons drank extensively; one-third of them were detained in the station, with the majority being detained repeatedly which arouses suspicion as to their dependence. 79 per cent of the registered persons were known to the police who had to intervene in their cases comparatively often and the company they kept was appraised negatively by the police 45 per cent had criminal records (with offences against property predominating) their effence however did not provide them money enough to replace employee’s wages. The first stage of introduction of the Act was to reveal persons liableto registration. The performance of the duty of registration met with most serious problems. Persons who reported themselves to be registered constituted less than a half of the total of those registered, this situation remaining unchanged even one year after the Act had entered into force. Even after that period, over a half of those newly registered were persons who had not been working for over a year and who thus should have been registered much earlier Some of those who reported themselves did it only because they needed a certificate of registration to settle some important personal matter A rather numerous category nearly one- third of the examined men consisted of those registered after having been punished by a transgresion board for failure in the duty of registration, and those reported by the police or public prosecutor’ s office Therefore, the police were explicitly involved in the process of picking out persons evading work. Also the realization of the entire second stage of dealing with the above persons - that of classification - arouses serious doubts. Index cards of a great number of persons lacked information essential for the realization of the Act, i.e. concerning certain facts about the registered person and the history of this previous employment. Among the vital decisions taken in relation to the registered persons is the recognition of the reason of their unemployment as justified or unjustified. A tendency became pronounced in these decisions to treat illness and prolonged formal transactions related to future work as valid excuses for not working and out to excuse working without formal employment. It appeared also that officials deciding in these matters enjoyed a certain degree of discretion when appraising the reasons of unemployment. The actions taken toward the registered persons assumed first of all the character unemploying: they consisted in obligating these persons to report again and inform about employment, or in referring them; therefore these actions failed to bring about any considerable effects; had the persons in question reported directly at the employment agency, the effects would have been identical. One-forth of the registered persons were directed to do work for public purposes. As many as two- thirds of them never even appeared to get the adress of the enterprise which such organized work, and 15 per cent reported at the workplace but failed to fulfil their duties. Thus directing to work for public purposes was of a trifle importance only; out of proportion with the effort put in the organizing of such work. Thoroughout the period included in the study, the names of 152 (7 per cent) of the registered men were entered in the list of persons who persistently evaded work. Punishment for infringement of the disscused Act was moved for in one third of cases. As shown by the picture of realization of the Act, the officials who apply it often face the registered men’s most complex life problems, that are difficult to appraise explicitly and to decide upon beyond dispute; besides, methods of successful circumvention or evasion of the provisions of the Act appear to have emerged. The appraisal of the functioning of the discussed Act has been done on two planes: both the realization of the legislator’s intentions and the social effects of its introduction other than intended have been analyzed. The legislator’s intentions are defined as coming to the assistance of those out of work and out of school who want work, and inducing to work those who fail to express this wish. In the statements of the Minister of Justice and of the deputy reporter during the parliamentary discussion, also such aims were formulated as: drawing up a record of persons evading work and thus getting knowledge as to the extent of this phenomenon; providing hands in cases of their shortage; and soothing the indignant public opinion which demanded radical measures to fight the phenomenon of the so-called social parasitism. The above intentions have been realized but to a slight degree. Cases of getting help from administrative agency were extremely rare, the agency playing but the role of an agent who directs clients on to the employment or medical agencies. After registration 44.5 per cent of the examined persons took a job and 37.6 per cent continued to work incessanuy for 6 months which is the condition of their names being stroken off from the register. The latter group proved to be "better" as regards selected social traits. According to our appraisal, these persons had greater chances and possibilities of and performing a job as compared with the remaining group; what’s more "inducing" them to work was frequently absolutely unnecessary. Registration failed to provide knowledge as to the size of the phenomenon of evasion of work, inconstancy being among its characteristics. The examined persons are often temporarily unemployed, this situation far from being permanent. Registration failed to improve the situation in the labour market: not only the number of those who found a job but also the total of those registered was too small as compared with the needs. Whether the public opinion has been soothed and satisfied by the introduction of the Act, we do not know. What we do know, is that among those registered there were hardly any persons whose unemployment particularly irritated the public opinion (e.g. black market and foreign currency dealers). A number of persons "evad.ing work" can always be" found, and the reasons for which some of them fail to take a job would hardly meet with social desapproval. Apart from the intended effects of any legal regulation, there are also those unintended which in the case of the discussed Act can be found in the following spheres: 1) the legal system: in the labour law (limitation of the principle of freedom of work), and in the penal law (the range of penalized acts has been broadened to include transgressions and offences provided in the Act; moreover, a penal law sanction was used as an instrument to solve a problem that belongs to the sphere of social an economic policy exclusively; 2) the sphere of political an social activities: an additional bureaucratic cell in labour exchange has been created in the case of alcoholics, intervention of the Act is but a seeming action, leaving the essence of the problem out of account; in the case of ex-convicts, the Act doubles the activity of other institutions (such person can obtain help in employment agencies or from their probation officers, and they are , induced" to take a job by their life situation or by the conditions on which they have been released from prison); 3) the sphere of social attitudes towards the law: failure to collect subpoenas and to appear when summoned could be observed among the registered persons which means that mechanisms of circumventing the Act emerged. In our opinion, the Act on the treatment of persons evading work is unnecessary. A separate and independent problem of persons who evade work does not exist. Instead, there is a number of various, partly overlapping problems: demand for labour, social frustrations of the crisis period, as well as alcoholism, delinquency disturbed socialization of the youth, failure to insure employes without setting the required formalities, problem of employment of the disabled. Also favourable phenomena and traits can be found here such e.g. the energy and initiative of those who want to work more effectively and to be paid better As shown by our study, , social parasitism , i.e. the actual staying out of work and living at the expense of others, can be found in a tiny percentage of registered persons.